Kiepert Triangles in an Isotropic Plane - Volenec, Vladimir; Kolar–Begović, Zdenka; Kolar–Šuper, Ružica (Sarajevo Journal of Mathematics, 2024)
In this paper the concept of the Kiepert triangle of an allowable triangle in an isotropic plane is introduced. The relationships between the areas and the Brocard angles of the standard triangle and its Kiepert triangle are studied. It is also proved that an allowable triangle and any of its Kiepert triangles are homologic. In the case of a standard triangle the expressions for the center and the axis of this homology are given. 2000 Mathematics Subject Classification. 51N25